CONSUMER PRACTICES FOR PURCHASE, STORAGE, AND PREPARATION OF POULTRY AND EGGS IN SELECTED NORTH AND SOUTH AMERICAN COUNTRIES: A PILOT STUDY - Kadri KOPPEL
Background:Poultry, eggs, and their products represent a potential food safety hazard. Although consumer practices related to these foods have been studied in various countries, little data exists from Latin America. Objectives: The objective of this pilot study was to provide initial data to characterize consumers' purchase, storage, handling, and preparation of poultry products and eggs in three countries: Argentina, Colombia, and USA. Methods: Consumers (n = 425 total) in each location completed a questionnaire about poultry products and egg purchase locations, storage conditions (i.e. refrigerator or freezer), preparation and handling practices, and managing leftovers. Results: The results indicated that in the USA most surveyed consumers purchased refrigerated eggs, whereas in Argentina (91%) and Colombia (84%) eggs typically were purchased at room temperature. Furthermore, almost all consumers in the USA stored eggs in the refrigerator, but 23% of Argentinian and 45.9% of Colombian consumers stored eggs at room temperature, which is potentially an unsafe practice. Some practices supported possible cross-contamination, for example washing raw eggs and poultry prior to cooking. Conclusions: These results are a first comparison across countries in the Americas of consumer poultry and egg practices and can serve as the basis for further research and development of food safety educational messages.